Synthesis of α-d-galactose-based azacrown ethers and their application as enantioselective catalysts in Michael reactions. (29th July 2016) - Rapi, Zsolt; Grün, Alajos; Keglevich, György; Stirling, András; Bakó, Péter
Abstract : Crown ethers derived fromd -galactose generated good to excellent enantioselectivities in a few Michael reactions under solid–liquid phase transfer conditions. Abstract : New chiral monoaza-15-crown-5 type macrocycles annelated to methyl 4, 6- O -benzylidene-α-d -galactopyranoside have been synthesized. These crown ethers proved to be efficient catalysts in a few asymmetric reactions under mild phase transfer catalytic conditions. Michael adducts were formed with good to excellent enantioselectivities, so the addition of diethyl acetamidomalonate to β-nitrostyrene took place with up to 92% ee, while the reaction of diethyl acetoxymalonate with chalcones proceeded with up to 99% ee. Using diethyl bromomalonate as the nucleophile, the chiral cyclopropane derivatives were formed in up to 99% ee with the addition to chalcone, in up to 78% ee in the reaction with benzylidene malononitrile, and in up to 76% ee in the reaction with 2-benzylidene-1, 3-diphenyl-1, 3-propanedione applying α-d -galactoside-based crown ethers as the catalysts. In the Michael addition, the substituents of the chalcone had a considerable impact on the outcome of the reactions. Quantum chemical calculations have also been employed to evaluate the origin of the stereoselectivities.